Vessel occlusion in three cultivars of Olea europaea naturally exposed to Xylella fastidiosa in open field. Issue 9 (19th June 2017) - De Benedictis, Maria; De Caroli, Monica; Baccelli, Ivan; Marchi, Guido; Bleve, Gianluca; Gallo, Antonia; Ranaldi, Francesco; Falco, Vittorio; Pasquali, Vittorio; Piro, Gabriella; Mita, Giovanni; Di Sansebastiano, Gian Pietro
Abstract: Xylella fastidiosa is a Gram‐negative, xylem‐limited, bacterium which is responsible, in Italy, for the olive quick decline syndrome (OQDS). The disease is caused by the subspecies pauca and emerged a few years ago in the Apulia province of Lecce, in the Salento peninsula, on Olea europaea plants . X. fastidiosa can infect different plant species and is well known in California as the causal agent of Pierce's disease on grape. Infections of susceptible hosts with X. fastidiosa are known to result in xylem vessel occlusions, water movement impairment, and accordingly to induce the typical desiccation symptoms. In this study, we investigated xylem vessel occlusions in healthy and naturally infected O. europaea plants grown in open field by analysing three olive cultivars widespread in the region that show different degree of susceptibility to the disease: the susceptible cultivars "Ogliarola salentina" and "Cellina di Nardò, " and the tolerant cultivar "Leccino." Our results show that occlusions were caused by tyloses and gums/pectin gels, and not by bacterial cell aggregates. Our data also indicate that occlusions are not responsible for the symptomatology of the OQDS and, as observed in Leccino plants, they are not a marker of tolerance/resistance to the disease.